Implementasi CRUD (Create, Read, Update, Delete) pada Aplikasi Toko Sembako Berbasis Visual Basic.NET dan MySQL - Adha, Nadya Atiqah; Rofiq, Ainur; Basatha, Rizky (Lembaga Yasin AlSys, 2025)
Advances in information technology have opened up great opportunities to increase efficiency and smooth operations in various sectors, including grocery stores. However, many grocery stores still use manual, error-prone, and time-consuming methods for managing inventory and recording sales transactions. To overcome this problem, a grocery store merchandising application was developed and interacted with a database using Microsoft Visual Studio and SQL Server. This application was designed to meet the needs of store owners, cashiers and customers. The main features developed include product management, inventory management, sales transactions, and sales reporting. Interface design using Windows Forms by prioritizing usability and data security. The design process involves several stages: user needs analysis, database design, feature implementation, testing, and refinement. The result of this design is a desktop application that can improve operational efficiency in grocery stores by providing faster and more accurate inventory and transaction management and reporting. real-time to support business decisions. Therefore, it is hoped that this application can be an effective solution for grocery stores to face operational obstacles in the digital era.